2000
DOI: 10.1001/archneur.57.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Using Serial Registered Brain Magnetic Resonance Imaging to Measure Disease Progression in Alzheimer Disease

Abstract: Registration of serial MRI volume images provides a powerful method of quantification of brain atrophy that can be used to monitor progression of AD in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(226 citation statements)
references
References 30 publications
11
214
0
1
Order By: Relevance
“…Using BBSI, brain atrophy rates on serial scans of 18 patients with AD were 2.37% Ϯ 1.11% per year compared with 0.41% Ϯ 0.47% per year in an age-matched and gender-matched control group. 89 Furthermore, the rate of atrophy correlated with the cognitive decline in AD based on the Mini-Mental State Examination scores implying the relevance of this marker to clinical progression. 90 In another study, which calculated volumes using automated techniques, the annual rate of change in the whole brain, temporal lobes, and the ventricle, identified higher rates of temporal lobe and whole brain atrophy and ventricular enlargement in 14 people with AD than 14 age-matched and gender-matched controls.…”
Section: Both Antemortem and Postmortem Mr Studies Indicate That Mr-bmentioning
confidence: 96%
See 1 more Smart Citation
“…Using BBSI, brain atrophy rates on serial scans of 18 patients with AD were 2.37% Ϯ 1.11% per year compared with 0.41% Ϯ 0.47% per year in an age-matched and gender-matched control group. 89 Furthermore, the rate of atrophy correlated with the cognitive decline in AD based on the Mini-Mental State Examination scores implying the relevance of this marker to clinical progression. 90 In another study, which calculated volumes using automated techniques, the annual rate of change in the whole brain, temporal lobes, and the ventricle, identified higher rates of temporal lobe and whole brain atrophy and ventricular enlargement in 14 people with AD than 14 age-matched and gender-matched controls.…”
Section: Both Antemortem and Postmortem Mr Studies Indicate That Mr-bmentioning
confidence: 96%
“…80 Two studies showed that MR-based volumetry techniques in AD may have enough power to measure the rate of structural change in the brain in a clinical trial setting if the magnitude of treatment effect is Ͼ10%. 89,97 The feasibility of MR-based volumetry as a treatment outcome measure in AD was tested in a multisite therapeutic trial of milameline, a centrally active muscarinic agonist. 98 Using a centrally coordinated quality control program for MRI, the hippocampal volume measurements were found to be consistent across sites, validating the feasibility of multisite acquisition MR-based volumetry in AD.…”
Section: Serial Mr Measurements Correlating With Clinical Disease Promentioning
confidence: 99%
“…The key attraction of incorporating MRI measures of progression is to provide a means of identifying diseasemodifying (slowing) effects of a therapy as opposed to temporary symptomatic effects. Although clinical outcomes remain paramount the idea is that imaging biomarkers of progression might provide evidence of disease-slowing earlier or more cost-effectively than clinical outcomes (which potentially require lengthy and complex trials) (6). Biomarkers are often referred to as possible "surrogate" outcome measures for clinical outcomes.…”
Section: Outcome Measures: Markers Of Progressionmentioning
confidence: 99%
“…The argument being, that if the treatment were to completely stop pathological progression then atrophy should slow to normal aging rates; with proportional effects on atrophy reflecting different therapeutic effect sizes. The variance in the AD rates is what determines the ability to detect change (power) and hence the sample sizes needed (6,12). Typically reported standard deviations of AD hippocampal atrophy rates are around 3-3.5%/yr for a one year study falling to 2-2.5%/yr with an 18 month study.…”
Section: Regional Measures: Hippocampusmentioning
confidence: 99%
“…In this map, contraction implies atrophy; expansion implies local growth or dilation. 54 A color map then displays these changes on the follow-up scan (FIG. 3).…”
Section: Brain Mapping As a Tool To Study Neurodegenerationmentioning
confidence: 99%